Implementasi Statistical Process Control pada Operasi Pengisian Produk Pangan Bubuk - Winiati Pudji Rahayu; Galih Nugroho; Andro Frando Situmorang (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Weight variability at pengisian operation of a food manufacturing company is a significant quality problem. Weight variability causes consumers get varied amount of products in each package. This research aims to implement statistical process control to reduce weight variability. Three sources of variability were analyzed: gage method, operator performance, and packaging weight. Analysis toward gage method using gage Repeatability and Reproducibility (R&R) analysis shows that gage method in sachet and box contributes to 3.55 and 1.30% variance of end product respectively. Analysis toward operator performance using weight adjustment analysis shows underadjustment (operator missed knob adjustment while average weight is out of control) is a significant variability source. Analysis toward packaging weight using consistency analysis in X ̅-R chart shows suplier B has out of control weight consistency. Tightening of product weight monitoring by operator with 15 minutes interval shows reduction in standard deviation from 0.0407 to 0.0298 and changes average product weight from 2.028 to 2.001 g, closer to target weight 2.000 g. Feasibility study for the solution is conducted by mapping operator’s activity in Gantt chart and shows that solution to tighten product weight monitoring by operator is feasible.